Over Kontrak Ruko Tinjauan Hukum Ekonomi Syariah di Majalaya Kabupaten Bandung - Latif, Ilman Abdul; Wibawa, Ginan (Journal of Islamic Economic Studies, 2025)
A legal relationship to meet need where one party does not have the necessary goods, and must rent them from other by paying rent to the who rents them for the enjoyment he gets from the leased good eithin a certain period of time. This study aims to determine the review of sharia economic law against shophouse over contract. Methods used Qualitative (Qual) with types of empirical research. The nature of this empirical juridical.  Data collection techique in this study is by conducting observation, interviews, and documentation in shophouse. Regarding the practice of renting between the person who gave the shophouse retal, namely the manager and the shophouse tenant, where the lease agreement is held verbally and in writing, however, if at the time of the lease, there was a disagreement with the initial agreement regarding the over contract of the shophouse tenant without beingnaware of the approved by the market manager where it should be used by tenant himself and not be allowed to over contract without shophouse. Knowledge and approval the of the market manager. Research result show that is valid, marked by meeting the terms and conditions of the rental agreement both the terms and condition for the musta'jir and mu'ajir parties.